Multiple-relaxation-time lattice Boltzmann analysis of entropy generation in a hot-block-inserted square cavity for different Prandtl numbers - Kashyap, Dhrubajyoti; Dass, Anoop K.; Öztop, Hakan Fehmi; Abu-Hamdeh, Nidal (Elsevier France-Editions Scientifiques Medicales Elsevier, 2021)
This work analyses the effects of three different Prandtl number fluids (Pr = 0.025, 5.83 and 151) on convective heat transfer inside a closed square cavity with an adiabatic left wall and three other cold walls. A centrally positioned square hot block with respective blockage ratios of 0.25 and 0.5 heats the cavity, which induces natural convection inside it for Grashof numbers Gr = 10(4), 10(5) and 10(6). Besides, two different cases of mixed convection based on the direction of moving right wall are investigated for varying Richardson numbers (0.01 <= Ri <= 100) at Gr = 10(4). We implement multiple-relaxation-time based thermal lattice Boltzmann model to study these flow configurations. The comprehensive analysis of the results suggests that the block size and Pr have a considerable influence on the flow and heat transfer behaviour. The average Nusselt number over the block surface (Nu(h)) over bar and total entropy generation throughout the cavity (S-tot) over bar increase with an increase in Pr and Gr due to the augmentation of convective heat transfer. For all three cases, (Nu(h)) over bar at BR = 0.25 is higher compared to BR = 0.5. In mixed convection, the heat transfer irreversibility mostly dominates the entropy generation at all Pr irrespective of Ri values as indicated by large average Bejan number. The present code is carefully validated with the well-established results obtained through conventional numerical techniques.
Keywords: Multiple-relaxation-time lattice Boltzmann method; Natural convection; Mixed convection; Prandtl number; Blockage ratio; Boundary conditions